Antibacterial spirooxindole alkaloids from Penicillium brefeldianum inhibit dimorphism of pathogenic smut fungi - Shi, Huajun; Jiang, Jinyan; Zhang, Hang; Jiang, Haimei; Su, Zijie; Liu, Dandan; Jie, Ligang; He, Fei (Frontiers in Microbiology, 2022)
Three new antibacterial spirooxindole alkaloids, spirobrefeldin A–C (1–3), together with four known analogs, spirotryprostatin M (4), spirotryprostatin G (5), 12β-hydroxyverruculogen TR-2 (6), and 12α-hydroxyverruculogen TR-2 (7), were isolated from terrestrial fungus Penicillium brefeldianum. The structures of new compounds were elucidated by extensive 1D, 2D NMR and Mass spectroscopic data, and their absolute configurations were determined by computational chemistry and CD spectra. The absolute configurations of spiro carbon C-2 in spirotryprostatin G (5) and spirotryprostatin C in literatures were reported as S, which were revised to R based on experimental and calculated CD spectra. All the compounds were evaluated for their antimicrobial activities towards Pseudomonas aeruginosa PAO1, Dickeya zeae EC1, Staphylococcus epidermidis, Escherichia coli and Sporisorium scitamineum. Compound 7 displayed moderate inhibitory activity toward dimorphic switch of pathogenic smut fungi Sporisorium scitamineum at 25 μM. Compounds 3 and 6 showed weak antibacterial activities against phytopathogenic bacterial Dickeya zeae EC1 at 100 μM.